The Effect Of Good Corporate Governance Implementation On Tax Avoidance Behavior - Christin Agustina; Agoestina Mappadang (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2022)
This research is based on the intention to see the extent of the influence of independent commissioners, institutional ownership audit committees, managerial ownership and the comparison of previous and current year tax avoidance on tax avoidance, and the relationship of good corporate governance to tax avoidance in companies. The occurrence of a phenomenon due to bad corporate governance that has an impact on the trend of tax avoidance that is carried out in a legal way as well as an illegal way is further exacerbated by the COVID-19 pandemic. The independent variable is measured by taking several variables in corporate governance. Tax avoidance is used as the dependent variable and is measured by CETR. The sample was taken by purposive sampling by collecting company data on the IDX totaling 73 from the same businesses in the property and real estate business in 2014-2020. The statistical analysis uses panel data regression analysis with Eviews 10 as the data processing application. The results show that independent commissioners do not significantly affect tax avoidance, the audit committee does not significantly affect tax avoidance, institutional ownership does not significantly affect tax avoidance, managerial ownership significantly affects tax avoidance, tax avoidance in the previous year period significantly affects tax avoidance in the current year period.